(3GdaQhY aj abg GdEeGe CMeO Hf MfHds - (3GHf oerapdM , eMeO Hf eadM Hf eMeO Hf eaQL, CHh YHO Gddg, TeS GdOjf GdebOSj GdQGejfj Ke GdUGdMj,J (B763 (3g` s ((3CMeO Hf YHO Gddg GdebOSi s)
(3ChdgG (B:s
(3bGd GdTjN Hf eadM GdebOSi GdMfHdi GdMeO ddg GdeJaVd Ydi Ndbg HcKQI GdCaVGd hGdfYe CeG HYO agPG cJGH ai Gdabg Ydi ePgH GdEeGe Hf MfHd GLJgOJ ai GNJUGQg hJMQjQg s
(3BNQgG (B:s
(3bGd GHf GdCKjQ ai bhdg (B" (3GdSjO Gddg (B" (3Ci GdPi JMb dg GdSjGOI cGfg cQg Cf jMeO ai hLgg hCMH GdJhGVY BNQ GdLRA GdChd Jjdhg ai ChGFd GdLRA GdKGfi Ef TGA Gddg JYGdi cJGH GdHjhY s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B44s
Keywords: (3Gdabg GdMfHdjs